New Developments in Laser Processing of Silicon Devices - Dirscherl, Manfred; Eßer, Gerd (Proceedings of SPIE Vol. 4977 Photon Processing in Microelements II, 2003)
Silicon is the standard material for the production of integrated circuits and one of the most important substrates for micro systems technology. It can be produced with an extraordinarily high purity, homogeneity and crystal perfection. Today, laser processing of silicon is becoming increasingly more interesting. This can be partly attributed to the evolution of frequency-converted solid state lasers which emit visible or ultraviolet radiation that is readily absorbed by silicon. Another reason for the growing interest in laser processing of silicon devices is that conventional technologies are approaching their limits. Especially laser cutting of thin silicon wafers as an alternative to mechanical sawing represents a very promising option for industrial applications. This paper shows current research results on laser processing of silicon. Besides laser cutting and ablation with frequency-tripled Nd:YAG lasers and Ti:Sapphire femtosecond lasers, laser welding of silicon with millisecond pulses is a focus of the presented work. When welding Si, the brittle behaviour of the material usually leads to thermally induced cracks. These cracks do typically not occur when cutting with short and ultrashort pulsed lasers. A controlled heating of the work piece can prevent cracks during welding with millisecond pulses as well. Together with laser cutting and welding, laser adjustment of silicon components by ultrashort pulse ablation of pre-stressed layer systems, which is also described in this paper, is another promising approach for high precision manufacturing of silicon micro devices.
LFT Import::2019-08-05 (978)
Keywords: Laser adjustment; Laser cutting; Laser welding; Silicon